Physical activity for antenatal and postnatal depression in women attempting to quit smoking: randomised controlled trial - Amanda Daley; Muhammad Riaz; Sarah Lewis; Paul Aveyard; Tim Coleman; Isaac Manyonda; Robert West; Beth Lewis; Bess Marcus; Adrian Taylor; Judith Ibison; Andrew Kent; et al. (BMC, 2018)
Abstract Background Antenatal depression is associated with harmful consequences for both the mother and child. One intervention that might be effective is participation in regular physical activity although data on this question in pregnant smokers is currently lacking. Methods Women were randomised to six-weekly sessions of smoking cessation behavioural-support, or to the same support plus 14 sessions combining treadmill exercise and physical activity consultations. Results Among 784 participants (mean gestation 16-weeks), EPDS was significantly higher in the physical activity group versus usual care at end-of-pregnancy (mean group difference (95% confidence intervals (CIs)): 0.95 (0.08 to 1.83). There was no significant difference at six-months postpartum. Conclusion A pragmatic intervention to increase physical activity in pregnant smokers did not prevent depression at end-of-pregnancy or at six-months postpartum. More effective physical activity interventions are needed in this population. Trial registration Current Controlled Trials ISRCTN48600346. The trial was prospectively registered on 21/07/2008.